Alliance of Matrix Metalloproteinase-9 Promoter-1562C/T Polymorphism and Metalloproteinase-9 Saliva Concentration of Iraqi Patients with Chronic Periodontitis - Atyaf Lateef Alturfa; Laith Sami Mehdi; Majida Sulaiman Aadai (Institute of Medico-legal Publications Pvt Ltd, 2021)
Matrix metalloproteinases (MMPs) are key enzymes responsible for matrix degradation, derived frompolymorphonuclear leukocytes, during the early stages of periodontitis. There is plenty of evidencefor the role of matrix metalloproteinases in the destructive processes of periodontal disease as a viabletarget in early diagnosis and chemotherapeutic approach. The aim of this study was to determine thelevels of salivary matrix metalloproteinase-9 (MMP-9) in patients with periodontitis and healthycontrols and the role of gene polymorphisms in the aetiology of the disease. Levels of MMP-9 insaliva was determined by enzyme linked immune sorbent assay (ELISA) technique in healthy subjectswithout any periodontal disease (n = 45) and in the patients with diagnosed periodontitis (n = 45).Gene Amplification, gel electrophoresis and genotyping were also carried out on MMP-9 gene. TheMMP-9-1562C/T appeared in three genotypes: CC, CT and TT, allele specific gene polymorphism wasamplified by PCR technique. The distribution of different genotypes in patients and controls for each ofMMP-9-1562C/T polymorphism was in a good accordance with Hardy-Weinberg equilibrium (HWE).Genotypes in both dominant and recessive models were non-significantly associated with periodontitis.Significantly higher salivary MMP-9 was observed in cases of periodontitis compared to healthy adults(p = 0.043). Salivary MMP-9 may serve as a biomarker of periodontal disease monitoring and aid inthe early detection of periodontitis.